Insights Into the Evolution of Staphylococcus aureus Daptomycin Resistance From an in vitro Bioreactor Model - Lasek-Nesselquist, Erica; Lu, Jackson; Schneider, Ryan; Ma, Zhuo; Russo, Vincenzo; Mishra, Smruti; Pai, Manjunath P.; Pata, Janice D.; McDonough, Kathleen A.; Malik, Meenakshi (Frontiers in Microbiology, 2019)
The extensive use of daptomycin for treating complex methicillin-resistant Staphylococcus aureus infections has led to the emergence of daptomycin-resistant Staphylococcus aureus strains. Although genomic studies have identified mutations associated with daptomycin resistance, they have not necessarily provided insight into the evolution and hierarchy of genetic changes that confer resistance, particularly as antibiotic concentrations are increased. Further, plate-dependent in vitro analyses that passage bacteria in the presence of antibiotics can induce selective pressures unrelated to antibiotic exposure. We established a continuous culture bioreactor model that exposed S. aureus strain N315 to increasing concentrations of daptomycin without the confounding effects of nutritional depletion. Samples were collected every 24 hours for a period of 14 days and minimum inhibitory concentrations were determined. Additionally, the collected samples were subjected to whole genome sequencing to monitor the acquisition of daptomycin resistance. The development of daptomycin resistance in N315 was associated with previously identified mutations in genes coding for proteins that alter cell membrane charge and composition. Although genes involved in metabolic functions were also targets of mutation, the common route to resistance relied on a combination of mutations at a few key loci. Tracking the frequency of each mutation throughout the experiment revealed that mutations need not arise progressively in response to increasing antibiotic concentrations and that most mutations were present at low levels within populations earlier than would be recorded based on SNP filtering criteria. In contrast, a serial passaged population showed only one mutation in a gene associated with resistance and provided limited detail on the changes that occur upon exposure to higher drug dosages. To conclude, this study demonstrates the successful in vitro modeling of antibiotic resistance in a bioreactor and highlights the evolutionary paths associated with the acquisition of daptomycin non-susceptibility. An understanding of the mechanisms underlying resistance and the evolutionary fates of different mutations within a system that more realistically mimics in vivo conditions will facilitate the development of new strategies to counter the problem of antibiotic resistance.